Land and Pessimistic Futures in Contemporary African American Speculative Fiction. Issue 1 (March 2020) - Dillender, Kirsten
Abstract : Little existing scholarship studies how relationships between blackness and the environment in contemporary speculative fiction represent or remedy antiblack behaviors. Jesmyn Ward's Sing, Unburied, Sing (2017) and N. K. Jemisin's Broken Earth trilogy (2015–2017) portray landscapes that perpetuate black vulnerabilities yet also accommodate affiliative relationships. These novels fully embrace pessimism to ask what happens when we acknowledge that structural racism continually denudes black futures. Rendering progress narratives false, they insist we repair the present before turning to the future, even if we must imagine the end of the world to do so.